2011
DOI: 10.1002/jbmr.379
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease and bisphosphonates induce osteonecrosis of the jaws in the rat

Abstract: Bisphosphonates (BPs) are medications used commonly to treat primary and metastatic bone cancer, as well as osteoporosis. Although BPs improve bone mineral density, reduce fracture risk, and reduce hypercalcemia of malignancy, some patients develop BP-related osteonecrosis of the jaws (BRONJ). This devastating complication is defined as clinically exposed bone in the maxillofacial region for more than 8 weeks. Despite an increasing number of BRONJ cases since first reported, the disease pathophysiology remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
219
2
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(258 citation statements)
references
References 61 publications
17
219
2
13
Order By: Relevance
“…The variable reproduction of osteonecrotic-like changes have been also reported in different murine models of ONJ and seems to be associated with the degree of surgical trauma (Marino et al 2011). Otherwise, empty lacunae, the other key feature in human and experimental osteonecrotic diseases (Okazaki et al 2009;Aghaloo et al 2011), were recognized widely in the bone sequestra and selectively in the superficial layer of submucosal bone in the alveolar socket. Interestingly, the number of empty lacunae in the submucosal bone significantly increased after long-term treatment, suggesting that this finding may be associated with the cumulative doses fixed in the alveolar bone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variable reproduction of osteonecrotic-like changes have been also reported in different murine models of ONJ and seems to be associated with the degree of surgical trauma (Marino et al 2011). Otherwise, empty lacunae, the other key feature in human and experimental osteonecrotic diseases (Okazaki et al 2009;Aghaloo et al 2011), were recognized widely in the bone sequestra and selectively in the superficial layer of submucosal bone in the alveolar socket. Interestingly, the number of empty lacunae in the submucosal bone significantly increased after long-term treatment, suggesting that this finding may be associated with the cumulative doses fixed in the alveolar bone.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, empty lacunae, the other key feature in human and experimental osteonecrotic diseases (Okazaki et al 2009;Aghaloo et al 2011), were recognized widely in the bone sequestra and selectively in the superficial layer of submucosal bone in the alveolar socket.…”
Section: Discussionmentioning
confidence: 99%
“…22 It was shown that, especially in the mandible, with progression of the severity of the BRONJ lesion, formation of new periostal bone increases. 20,22,23 In a periodontal disease induced BRONJ rat model, Aghaloo et al 24 reported increased periosteal new bone formation and wider alveolar bone on microCT images. Intermittent parathyroid hormone administration was also shown to induce an increase in alveolar bone formation in rats.…”
Section: Discussionmentioning
confidence: 99%
“…BRONJ in patients taking oral BPs for osteoporosis is rare, estimated at 0.001% to 0.1%. 78 The pathogenesis of BRONJ is not completely defined, but currently, two main hypothesis explain the mechanism for the complication of BP therapy. The first explains the pathology in terms of the osteoclastic-inhibiting effect of this class of drug on the cessation of bone remodelling and bone turnover.…”
Section: Bisphosphonate-related Osteonecrosis Of the Jawmentioning
confidence: 99%